2004
DOI: 10.1002/cncr.20567
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of p53 and MIB‐1 in transitional cell carcinoma of the urinary bladder with regional lymph node involvement

Abstract: BACKGROUNDThe effect of p53 protein expression and MIB‐1 proliferative activity on survival and chemotherapeutic response in patients with lymph node (LN)‐positive transitional cell carcinoma (TCC) of the urinary bladder remains unclear. The objective of this study was to assess the ability of these markers to predict disease‐associated outcomes and response to chemotherapy in a cohort of patients with LN‐positive TCC.METHODSThe authors examined the expression of p53 and MIB‐1 in the LN metastases from 139 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Tumors with a high Ki-67 LI are frequently more aggressive than those with low Ki-67 LI 28. In addition, factors involved in angiogenesis such as VEGF are associated with tumor growth and metastasis 17-19.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors with a high Ki-67 LI are frequently more aggressive than those with low Ki-67 LI 28. In addition, factors involved in angiogenesis such as VEGF are associated with tumor growth and metastasis 17-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, most patients in that series had locally advanced or node-positive disease. Frank et al (14) examined the expression of Ki-67 in the lymph node metastases from 139 patients who underwent cystectomy for TCC at their institution and found no association between Ki-67 and disease-related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This might be especially true in patients with PUNLMP and NILGC, whereas Aurora-A staining seems to be less useful in NIHGC and Cis. Several authors have shown implication of Aurora-A in carcinogenesis, demonstrating overexpression in human gastric carcinoma cell lines, primary gastric carcinoma and hepatocellular carcinoma [4,10,11,14,25]. As a matter of fact, Aurora-A regulates spindle cell assembly in mitosis and interferes in centrosome maturation.…”
Section: Discussionmentioning
confidence: 99%